Impact of climate change and variability on the occurrence and distribution of Trypanosoma vectors in The Gambia - Kargbo, Alpha; Dafka, Stella; Osman, Aamir M.; Koua, Herve Kouakou; Vieira, Rafael F. C.; Rocklöv, Joacim (Parasitology research, 2025)
Extreme weather events can lead to infectious disease outbreaks, especially those spread by hematophagous flies, and The Gambia is particularly vulnerable to climate change. To the best of our knowledge, no one has ever documented the relationship between climate variability and change and the distribution of the hematophagous flies belonging to the families Glossinidae, Tabanidae, and Stomoxyinae. This paper aims to study the association of temperature and humidity on the distribution of the above species and their families in The Gambia in the recent past and to provide predictions of species abundance and occurrence in the future. A line transect survey was carried out in all the administrative regions of The Gambia to study the prevalence of the flies. Generalized additive models were used to analyze the relationships between the distribution of the insects and their families and the variability in climate conditions in the recent past and in three different future periods. Regarding the recent past, our results show that temperature has significantly impacted the presence of Glossinidae and Tabanidae species, with maximum temperature being the most important factor. Relative humidity was also statistically significantly associated with Tabanidae species. None of the climate variables was found to be associated with the Tabanus par and Tabanus sufis. Minimum temperature and relative humidity were statistically significantly associated with Glossina morsitan submorsitan, while maximum temperature was statistically significantly associated with Atylotus agrestis and Stomoxys calcitrans. Only relative humidity was statistically significantly associated with the Glossina palpalis gambiense. As for the future projections, the results show that rising temperatures impacted the distribution of Tabanus species, Glossina species, and Stomoxys calcitrans in The Gambia. The distribution of Trypanosoma vectors in The Gambia is mostly influenced by maximum temperature. The research’s conclusions gave climate and public health policymakers crucial information to take into account.
Gesehen am 03.09.2025